The Impact of Factors of Success on the In-House Software Development for Preserving Tacit Knowledge: Survey - Shbair, Mohammed W; AlSarraj, Wael; Kahloot, Khalid (Arab Journal for Sciences and Research Publishing, 2016)
Factors of success are aimed to provide knowledge-intensive organisations to better manage their knowledge value. There are multiple ways to capture organization’s knowledge and make it available to all their members while it is not easy to capture/share the tacit knowledge among the stakeholders. The purpose of this study was to investigate the impact of factors of success on the in-house software development for preserving tacit knowledge. We conducted a survey to study the impact of these five factors on the tacit knowledge sharing between the developers within the in-house software development environment. This paper is firstly exploring the definition of the knowledge and introducing the types of knowledge those are explicit and tacit knowledge. We discuss the in-house software development concept in which the non-IT organizations may need to develop their own software internally with no need to have a third party software development organization. For tacit knowledge sharing, we considered four factors reviewed in other researches and we added to them the pair programming as a practice. Case study is local bank in Palestine. Based on the results we have, it is confirmed the hypothesis of a positive impact of factors of success on the process of knowledge sharing.